1972
DOI: 10.1017/s0021859600025910
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mixtures of dwarf sorghum and beans (Phaseolus vulgaris) with particular reference to plant population

Abstract: SUMMARYAn experiment is described in which the possible yield benefits of mixing dwarf sorghum and beans were examined under intensive farming conditions. A ‘replacement series’ of pure sorghum, two-thirds sorghum/one-third beans, one-third sorghum/twothirds beans and pure beans was used at four plant populations. A high level of nitrogen was applied to the sorghum to eliminate the effects of nitrogen transfer from the beans.Yields of the mixtures were up to 55% higher than could be achieved by growing the cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 4 publications
7
26
1
Order By: Relevance
“…These findings are in agreement with those of Osiru and Willey (1972) who reported that when component crops are present in approximately equal numbers, productivity and efficiency appear to be determined by the more aggressive crop, usually the cereal.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with those of Osiru and Willey (1972) who reported that when component crops are present in approximately equal numbers, productivity and efficiency appear to be determined by the more aggressive crop, usually the cereal.…”
Section: Discussionsupporting
confidence: 93%
“…The yield advantage of intercrops is a reflection of a better use of resources than monocultures (Osiru and Willey, 1972;Spitter, 1980;Trenbath, 1986). Nitrogen fixation is undoubtedly one important factor in the advantage of legume/nonlegume intercrops or pasture mixtures (Harper, 1977;Vallis, 1978;Willey, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Competition occurred from direct competition for soil moisture (O'Donnell & Coaker, 1975), plant nutrients and light (Ryan et al, 1980). These effects have been experienced in other mixed cropping situations but the combined yields of the 2 crops can often be higher than those of either crop grown in monoculture (Evans, 1960;Evans & Sreedharan, 1962;Grimes, 1963) mainly due to greater root interpenetration between the crops and more efficient use of incident radiation (Osiru & Willey, 1972;Trenbath, 1974). Further work is required on the agronomy of intercropping brassicas to evaluate the most cost-effective spacings to provide acceptable yields and reduce insecticidal treatments, and on the use of intercropping generally as a cultural method for insect pest management.…”
Section: Discussionmentioning
confidence: 99%